Influence of Traditional Wall Façade from Taneyan Lanjhang House to Thermal Sensation - Bastedo, Andreas; Larasati Z, Mentari Murti; Hariyanto, Agus Dwi (Universitas Sebelas Maret Surakarta, 2024)
Of the various ethnic groups that comprise Indonesia, Madurese ethnic belongs to the top five in ethnic group population numbers in Indonesia. As an ethnic group, Madurese developed a traditional settlement called natively Taneyan Lanjhang (TL). TL is described as a specific pattern settlement that follows local and Islamic-influenced cultural norms. This research aims to find local wisdom properties in tectonics configuration in Bangsal housing unit concerning thermal comfort and sensation aspect of a vernacular design. The study is using quantitative method with field observation using lidar scanner, hot-wire anemometer and model simulation using computational fluid dynamics. The final result of the study is finding a correlation between closing and opening wall configuration related to thermal comfort defined by airflow, temperature and relative humidity parameter.